Cannibalism of Decapod Crustaceans and Implications for Their Aquaculture: A Review of its Prevalence, Influencing Factors, and Mitigating Methods. Issue 1 (2nd January 2017) - Romano, Nicholas; Zeng, Chaoshu
ABSTRACT: The prevalence of cannibalistic behavior among many commercially important decapod crustaceans is one of the biggest limiting factors to their culture productivity and profitability in aquaculture. Various biotic and abiotic factors influence cannibalism including stocking densities, molt status, size heterogeneity, photoperiod, light intensity, and availability to refuge and food; however, their relative efficacies are often species or stage dependent. For instance, although generally penaeid shrimp are seldom cannibalistic when food and space are sufficient, this does not apply to many crab, lobster, and some crayfish species. This review will first discuss the cannibalistic prevalence among commercially important crustacean species followed by a brief review on the current knowledge regarding chemical cues that trigger cannibalism. The main focus will then be on various mitigating methods to improve survival for each of the three main aquaculture phases, that is hatchery, nursery, and grow-out, respectively. Throughout, areas in which one method may have applications to other species or life stages will be highlighted. A final section discusses possible future directions that include individually farming high-value crustaceans and the potential to manipulate hormones associated with aggression. It is hoped that such discussions as well as identifying knowledge gaps will prompt research to help expand and diversify the crustacean farming industry.